Fathers and Gender Traditionalism: Perception of Inequality and Life Roles - Paterna, Consuelo; Martínez, Carmen (The Spanish Journal of Psychology, 2006)
Men’s discourse about the paternal role is changing significantly. Despite the fact that men still perceive themselves as being responsible for the family’s economical protection and the children’s discipline, they face increasing demands for more involvement in childcare. From this perspective, this work analyzes the traditional view of gender roles and the perception of inequality in a sample of 95 employed fathers, as well as the various levels of satisfaction with other life roles and their relevance as a function of some gender and sociodemographic variables. The results show that men do not maintain a very traditional gender ideology with regard to role distribution and they still consider the paternal role and feelings as the most important thing in their lives. However, the couple relationship gives them the most satisfaction. Level of traditionalism and age were the two significant predicting variables of perception of inequality of men and women.